Research and Practices in Water Quality - Teang Shui Lee (IntechOpen, 2015)
Water quality refers to the chemical, physical, biological, and radiological characteristics of water. It is a measure of the condition of water for the purposes intended for. It is most frequently used by reference to a set of standards against which compliance can be assessed. The most common standards used to assess water quality relate to health of ecosystems, safety of human contact and potable drinking water. A range of diverse topics in the field of water quality modelling, statistical evaluation and guidelines pertaining to the best management practices in different locations around the world is given herein. Modelling of water quality in rivers and lakes, statistical methods and membrane filter performance are subject matters of interest considering in-situ water, potable water, water re-use, etc.
English
Keywords: Engineering; Physical Sciences; Engineering and Technology; Ecohydrology; Environmental Engineering